Robert Merton's thinking on the development of knowledge and science: The sociology of science (Revista Contexto & Educação, 2023)
This article aims to present and reflect some main Robert Merton's ideas, who is considered by countless researchers to be the “father of the Sociology of Science”. Merton's sociological studies take science as a distinctive social activity and one with a characteristic ethos. Several of these studies started in the first half of the century XX, however, reflective reading of some of his main works and articles shows that many of his ideas remain current and help us to understand how support for science is ensured by appropriate cultural conditions, why it is important to examine those controls that motivate scientific careers, that select and prestige certain scientific disciplines and reject others. We want to believe that this work can engender interesting critical discussions in the Basic Education classroom, helping to transform naive and rooted conceptions about scientific practice.
Keywords: Sociology of Science; Robert Merton; Scientific Education.